2014
DOI: 10.1037/a0035657
|View full text |Cite
|
Sign up to set email alerts
|

Cross-situational word learning in the right situations.

Abstract: Upon hearing a novel word, language learners must identify its correct meaning from a diverse set of situationally relevant options. Such referential ambiguity could be reduced through repetitive exposure to the novel word across diverging learning situations, a learning mechanism referred to as cross-situational learning. Previous research has focused on the amount of information learners carry over from 1 learning instance to the next. In the present article, we investigate how context can modulate the learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 23 publications
8
60
1
Order By: Relevance
“…Trueswell et al's (2013) choice of four foils made it likely that prior selections were repeated, leading them to potentially underestimate what people were learning from incorrect trials. Dautriche and Chemla (2014) decreased the number of foils, and found that people were now above chance in selecting the correct referent even after an incorrect previous encounter.…”
Section: 2 How Do People Learn Words In the Cross-situational Paradmentioning
confidence: 95%
See 2 more Smart Citations
“…Trueswell et al's (2013) choice of four foils made it likely that prior selections were repeated, leading them to potentially underestimate what people were learning from incorrect trials. Dautriche and Chemla (2014) decreased the number of foils, and found that people were now above chance in selecting the correct referent even after an incorrect previous encounter.…”
Section: 2 How Do People Learn Words In the Cross-situational Paradmentioning
confidence: 95%
“…Others have proposed hybrid accounts: For example, there are memory-based accounts in which such inferences are made over stored episodes of situations in long-term memory (Dautriche & Chemla, 2014). Bayesian accounts take a hypothesis-testing approach, but evaluate multiple probabilistic hypotheses simultaneously to find the most likely mapping given the data (Frank, Goodman, & Tenenbaum, 2009).…”
Section: 2 How Do People Learn Words In the Cross-situational Paradmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that children's ability to cope with competition could depend on higher-order properties of the context in which that competition occurs. Recent cross-situational learning studies have shown that adults who encountered novel nouns in themed referential contexts where all of the objects were from the same category (e.g., animals, clothing, things in the kitchen) retained more information about the potential referents for each word across observations (Dautriche & Chemla, 2014) and demonstrated higher rates of word learning (Chen & Yu, 2015;Dautriche & Chemla, 2014) than did adults who encountered the same nouns in non-themed contexts involving unrelated objects. Moreover, the advantage of themed over non-themed contexts held even when the former involved greater competition between referents because individual distracter referents co-occurred more frequently with the target (Chen & Yu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that under at least some circumstances, both adults and children can use cross-situational information to identify the referents of new words (e.g., Akhtar & Montague, 1999;Childers, 2011;Childers & Paik, 2009;Dautriche & Chemla, 2014;Gillette, Gleitman, Gleitman, & Lederer, 1999;Scott & Fisher, 2012;Smith, Smith, & Blythe, 2011;Smith & Yu, 2008;Yu & Smith, 2007, 2011. For instance, Smith and Yu (2008) presented 12-and 14-month-olds with a series of training trials in which pairs of novel objects were accompanied by two novel labels.…”
Section: Introductionmentioning
confidence: 99%